PEMANFAATAN KONSEP MODAL SOSIAL DALAM PENGELOLAAN OBYEK WISATA PANTAI KEDUNGU, DESA BELALANG KABUPATEN TABANAN (Studi Kasus: Obyek Wisata Pantai Kedungu, Desa Belalang Kabupaten Tabanan) - Pradnyana Putra, Agus Yogi (CITIZEN CHARTER, 2014)
ABSTRAK Social capital is the social adhesive for every individual in the form of a network of the trust and norms so, that will be a profitable cooperation to get a common goal. Social capital will be expanded if used together and will be lost if not used with values, norms and trust each other. Either between individuals or groups of organizations. The purpose of this research is to know the uses of social capital in the management of tourist attractions, Kedungu Beach. This research use the qualitative study. Study of data colletions used the interview’s study. Based on this study, social capital is needed in the way to manage Kedungu Beach as the tourist attractions. Based on these research results, concepts of social capital needed in the management of Kedungu Beach tourim object so that the problem can be resolved with limited funds, owned by the Government of the Belalang Village as the main tourist beach manager of Kedungu Beach. Keywords: social capital, management Kedungu Beach tourism